INTERACTIVE METHODS – IN QUALITY EFFICIENCY AND RESULTS OF TRAINING - Kayumov Sh.Sh. (Web of Journals Publishing, 2023)
The use of innovative technoligies in the field of higher education is currentlyan urgent task. The article considers the use of the interactive teaching method “brain - storming” in the educational process of higher educational institutions.
Keywords: Innovative technoligies, interactive teaching methods, “brain - storming”, group exercise.